2019
DOI: 10.3389/fpsyg.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

A Non-linear Relationship Between Selective Attention and Associated ERP Markers Across the Lifespan

Abstract: The ability to selectively attend to task-relevant information increases throughout childhood and decreases in older age. Here, we intended to investigate these opposing developmental trajectories, to assess whether gains and losses early and late in life are associated with similar or different electrophysiological changes, and to get a better understanding about the development in middle-adulthood. We (re-)analyzed behavioral and electrophysiological data of 211 participants, who performed a colored Flanker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 98 publications
(143 reference statements)
5
37
1
Order By: Relevance
“…We did not perform the state-of-the-art neurophysiological measurements in the current study; hence we are unable to determine which processes were optimized by the exergame intervention. Reuter et al (2019) found that cognitive processing speed (P3 latency) is the only significant predictor of response speed in children at the Flanker test. The authors further note that cognitive control (frontal N2 and P3 amplitude), and cognitive update (parietal P3) are important predictors of response accuracy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We did not perform the state-of-the-art neurophysiological measurements in the current study; hence we are unable to determine which processes were optimized by the exergame intervention. Reuter et al (2019) found that cognitive processing speed (P3 latency) is the only significant predictor of response speed in children at the Flanker test. The authors further note that cognitive control (frontal N2 and P3 amplitude), and cognitive update (parietal P3) are important predictors of response accuracy.…”
Section: Discussionmentioning
confidence: 92%
“…The authors further note that cognitive control (frontal N2 and P3 amplitude), and cognitive update (parietal P3) are important predictors of response accuracy. According to Reuter et al (2019) findings, exergame may had primarily improved information processing speed (P3 latency). As there were no differences between the groups in the accuracy response, we cannot assert to have equally affected the cognitive control (frontal N2 and P3 amplitude) and cognitive updating (parietal P3).…”
Section: Discussionmentioning
confidence: 98%
“…Selective attention allows to successfully focus on goal relevant information while inhibiting irrelevant information. As such selective attention is part of inhibitory control (Reuter et al, 2019). In this study, patients were presented 80 sets of arrows as a stimulus (central arrow as target stimulus surrounded by other distractor arrows).…”
Section: Methodsmentioning
confidence: 99%
“…Another observation of the review is that N170 amplitude and latency and P1 latency in response to faces decrease with increasing age [ 77 , 81 , 82 ], consistent with prior reports [ 95 , 108 ]. The decrease across age in P1 and N1 latency and N2 amplitude in response to the Flanker task demonstrated in a study in this review [ 48 ] has also recently emerged as a finding of a study conducted after this review search investigating developmental changes of selective attention [ 109 ].…”
Section: Discussionmentioning
confidence: 86%